2010
DOI: 10.1007/s11368-010-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activity facilitates phosphorus adsorption to shallow lake sediment

Abstract: Purpose The phosphorus (P) level in sediments is one of the major indicators of the eutrophication of lakes. Little information is available on the effect of microbial activity on P adsorption in shallow lake sediments. In this study, we evaluated the effect of microbial activity on the adsorption of P to sediments in a shallow lake. Materials and methods The effect of microbes on P adsorption by lake sediment was examined using an incubation experiment. Sediment samples were collected from a eutrophic lake an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that microbial processes are involved in the P flux between sediment and overlying water [13][14][15]. In addition, Boström et al [33] found that microbial biomass P accounts for up to 13% of total P in the surface sediment of Lake Vallentunasjön.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that microbial processes are involved in the P flux between sediment and overlying water [13][14][15]. In addition, Boström et al [33] found that microbial biomass P accounts for up to 13% of total P in the surface sediment of Lake Vallentunasjön.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been evidence that biotic processes mediated by microorganisms are also involved in P cycling [13][14][15]. Therefore, any factors affecting the growth of microorganisms should also be expected to influence P cycling at the sediment/water interface.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of P can be taken up by microorganisms in oxic conditions and transformed to cell biomass, particularly polyphosphate, which is the stored form of P in microbial cells (Huang et al, 2011). This phenomenon would both encourage continued flux of P to the water column via diffusion, and return P to the sediment as algae die and fall to the lake bottom.…”
Section: The Interrelationship Of Algae and Lake Nutrient Dynamics: Amentioning
confidence: 99%
“…Studies have also investigated the role of microbial activity in the sorption of chemicals to sediment, and how this may change due to variations in, for example, temperature and redox (e.g. Huang et al 2011). Further research is likely to focus on improving our understanding of chemical sorption and desorption to sediment under changing environmental conditions, including the role of changing flow regimes such as floods (Wölz et al 2010), and the role of thermodynamic and kinetic processes.…”
Section: Sediment-chemical Interactionsmentioning
confidence: 99%